Upper limb rehabilitation in children with unilateral cerebral palsy - Dequeker, Griet; Mailleux, Lisa (Belgian Journal of Paediatrics, 2023)
Children with unilateral cerebral palsy experience difficulties with unimanual and bimanual functions, impeding self-care independence in daily life. Hence, research aimed at improving upper limb function has increased tremendously throughout the last decade. In this manuscript, we will provide an overview of all evidence-based, non-surgical therapy models intended to improve upper limb function in children with unilateral cerebral palsy, described according to the International Classification of Functioning, Disability and Health framework. The strongest level of evidence refers to activity-based interventions like constraint-induced movement therapy, bimanual training and goal-directed training. Interventions targeting body structures or functions, such as muscle strengthening, taping, splinting or casting, are less well investigated and should at this point be considered as assistive interventions with therapy goals on the level of body structure and function. Limited evidence exists on the efficacy of participation-based interventions. Finally, environmental factors can further shape the therapy model by providing the therapy in the home setting or a camp environment, while personal factors may influence the response to treatment.